2015
DOI: 10.1111/cbdd.12590
|View full text |Cite
|
Sign up to set email alerts
|

Enrichment Assessment of Multiple Virtual Screening Strategies for Toll‐Like Receptor 8 Agonists Based on a Maximal Unbiased Benchmarking Data Set

Abstract: Toll-like receptor 8 agonists, which activate adaptive immune responses by inducing robust production of T-helper 1-polarizing cytokines, are promising candidates for vaccine adjuvants. As the binding site of toll-like receptor 8 is large and highly flexible, virtual screening by individual method has inevitable limitations; thus, a comprehensive comparison of different methods may provide insights into seeking effective strategy for the discovery of novel toll-like receptor 8 agonists. In this study, the perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 56 publications
0
8
0
Order By: Relevance
“…Indeed, MUV relies on the availability of experimental data and is restricted to well-studied targets. The authors subsequently proposed the Maximum Unbiased Benchmarking Data sets (MUBD, see section Benchmarking Databases) that was applied to GPCRs (Xia et al, 2014 ), HDACs (Xia et al, 2015 ; Hu et al, 2017 ) and Toll-like receptor 8 (Pei et al, 2015 ). The MUBD-DecoyMaker algorithm relies on both a minimal and required topological dissimilarity ( sims ) between decoy and active compounds, but makes use of an additional criterion that minimizes the simsdiff parameter, i.e., ensures that decoy and active compounds are as similar as possible.…”
Section: Discussion and Recommendationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, MUV relies on the availability of experimental data and is restricted to well-studied targets. The authors subsequently proposed the Maximum Unbiased Benchmarking Data sets (MUBD, see section Benchmarking Databases) that was applied to GPCRs (Xia et al, 2014 ), HDACs (Xia et al, 2015 ; Hu et al, 2017 ) and Toll-like receptor 8 (Pei et al, 2015 ). The MUBD-DecoyMaker algorithm relies on both a minimal and required topological dissimilarity ( sims ) between decoy and active compounds, but makes use of an additional criterion that minimizes the simsdiff parameter, i.e., ensures that decoy and active compounds are as similar as possible.…”
Section: Discussion and Recommendationsmentioning
confidence: 99%
“…New databases were designed with an increasing complexity in the decoys selection methodologies (see section Benchmarking Databases). Nowadays, benchmarking databases are widely used to evaluate various VS tools (Kellenberger et al, 2004 ; Warren et al, 2006 ; McGaughey et al, 2007 ; von Korff et al, 2009 ; Braga and Andrade, 2013 ; Ibrahim et al, 2015a ; Pei et al, 2015 ) and to support the identification of hit/lead compounds using LBVS and SBVS (Allen et al, 2015 ; Ruggeri et al, 2015 ).…”
Section: The History Of Decoys Selectionmentioning
confidence: 99%
“…Five compounds were finally selected for biological studies and one compound (code MolPort-001-796-266, Table 2 ) was confirmed as TLR2 antagonist. For TLR8 [ 59 ], while LigandScout was also used to obtain pharmacophore models within a sophisticated protocol to optimize VS of TLR8 agonists (see Section 4.5 ).…”
Section: Virtual Screening Protocols and Techniquesmentioning
confidence: 99%
“…Six new compounds with three new chemical scaffolds were identified as TLR7 antagonists with activities within the µM range ( Table 2 ). In the case of TLR8 [ 59 ], in order to generate ROCS queries, the authors performed an alignment of six crystal ligands as initial molecules. The results were ranked using the “ShapeTanimoto” and the “TanimotoCombo” scores.…”
Section: Virtual Screening Protocols and Techniquesmentioning
confidence: 99%
“…All the constructed models along with multiple scoring functions were evaluated for their screening power by retrospective small-scale virtual screening. Specifically, the evaluation was based on a benchmarking set generated by our in-house MUBD-DecoyMaker (Xia et al, 2014), a tool that had effectively facilitated VS campaigns against multiple targets (Huang et al, 2016;Pei et al, 2015;Xia et al, 2015). Apart from the screening power, the binding mode proposed by the optimal model was explored.…”
Section: Introductionmentioning
confidence: 99%